ROLE OF MORTGAGE LENDING IN DEVELOPMENT OF THE WORLD FINANCIAL MARKET - R. Khusikhanov (Вестник университета)
At the present stage of development of the world economy mortgage lending is the effective instrument of development of the financial markets of foreign countries. In article role of a mortgage in development of the world financial market under the influence of global crisis is analysed.